An active biodegradable layer-by-layer film based on chitosan-alginate-TiO2 for the enhanced shelf life of tomatoes. (December 2022) - Perera, Kalpani Y.; Sharma, Shubham; Duffy, Brendan; Pathania, Shivani; Jaiswal, Amit K.; Jaiswal, Swarna
Abstract: This work aims at developing biodegradable active chitosan-alginate layer-by-layer bio-nanocomposite film with TiO2 NPs using the solvent casting method followed by CaCl2 crosslinking for food packaging applications. The developed films enhanced the tensile strength and elongation at break by 14.76 and 2 folds (p < 0.05) respectively. The UV barrier properties of CH-SA-0.3%TiO2 film increased by 88.6%, while the film transparency decreased by 87.23%. All films showed antimicrobial activity against foodborne pathogens E. coli, S. aureus, S. typhi, and L. monocytogene . The film with 0.1%TiO2 showed the complete killing of gram-positive bacteria. The CH-SA-0.1%TiO2 film was completely biodegraded during the 3 months. The CH-SA-0.3%TiO2 film showed an increase in the shelf-life up to 8 days with stable pH, total soluble solids, and weight with no bacterial growth. Owing to their improved mechanical, UV barrier, antibacterial, and biodegradability properties the prepared films could be considered a potential candidate for fresh produce packaging. Highlights: Development of biodegradable active chitosan-alginate layer-by-layer film. CH_SA_0.2%TiO2 film showed enhanced mechanical and UV barrier properties. The film with 0.1%TiO2 showed the complete killing of Gram-positive bacteria. Complete biodegradation of CH_SA_0.3%TiO2 film within 3 months. CH_SA_0.3%TiO2 LBL film prolonged the shelf-life of tomatoes by up to 8 days.